Nine of 16 stereoisomeric polyhydroxylated proline amides are potent β-N-acetylhexosaminidase inhibitors. - Ayers, B; Glawar, A; Martínez, R; Ngo, N; Liu, Z; Fleet, G; Butters, T; Nash, R; Yu, C; Wormald, M; Nakagawa, S; Adachi, I; et al. (2014)
All 16 stereoisomeric N-methyl 5-(hydroxymethyl)-3,4-dihydroxyproline amides have been synthesized from lactones accessible from the enantiomers of glucuronolactone. Nine stereoisomers, including all eight with a (3R)-hydroxyl configuration, are low to submicromolar inhibitors of β-N-acetylhexosaminidases. A structural correlation between the proline amides is found with the ADMDP-acetamide analogues bearing an acetamidomethylpyrrolidine motif. The proline amides are generally more potent than their ADMDP-acetamide equivalents. β-N-Acetylhexosaminidase inhibition by an azetidine ADMDP-acetamide analogue is compared to an azetidine carboxylic acid amide. None of the amides are good α-N-acetylgalactosaminidase inhibitors.